Comparative Analysis of Acute Physiological Responses between Short and Middle Distance Swimming Athletes with Physical Loading Test - M. Ali Machfud; HariSetijono; Lilik Herawati; Muchammad Rif’at Fawaid As’ad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Indonesia’s swimming achievements are still far from that of other countries. Among other things, at the 2018Asian Games, Indonesia did not succeed in getting a single medal. If not improved, Indonesia’s swimmingperformance will get worse. One of the innovations is to identify the physical abilities and physiologicalresponses of an athlete through a physical loading test. This study aims to analyze the differences in acutephysiological responses between short and middle distance swimming athletes through continuous andinterval high intensity physical test. The sample of males aged 14-18 years consisted of the short distance(n=12) and middle distance (n=12) swimmers. Participants did a high intensity physical test with anergocycle for 21 minutes with a 7-minute warm-up and 3-minute cool down, intervally, and without restingfor continuous test. The variables studied included resting pulse rate, blood lactate, leg and shoulder musclestrength, arm andleg power. Data collected inbefore (pre) and after(post) physical test. The results showedthat the short distance swimmers had greater increase inlactate level and pulse rate in both physical tests.The leg power decreased significantly in the short distance swimmer when performed continue physical test,whereas the middle distance swimmer when performed interval physical test. The conclusion of this studywas to differ the leg power as acute physiology response for swimmers is more appropriate using continuousor interval high intensity physical test. Based on these results, training program for swimmer type can bedeveloped. However, further research is still needed to enhance the swimmers performance.